Korelasi Buku Teks Sejarah dengan Kemampuan Literasi Membaca Siswa - Juniar, Arinda Seva; Kusmarni, Yani; Sumantri, Yeni Kurniawati (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Various survey results indicate that the reading literacy skills of Indonesian students are still relatively low. However, reading literacy is a part of a set of skills and abilities that are essential in the 21st century. One of the factors influencing students' reading literacy skills is the source of reading materials. In the context of education, reading materials are closely linked to learning resources. In Indonesia, the majority of schools and students rely on textbooks as their primary learning resources. This is also the case in public high schools in Cimahi City. Therefore, the researcher was motivated to conduct a study to investigate the potential relationship between the use of textbooks as historical learning resources and students' reading literacy skills. The research method employed is correlation analysis. The study population consists of public high school students in Cimahi City, with a sample size of 380 students. Data was collected using a Likert-scale questionnaire. The research findings demonstrate a significant, positive correlation at a strong level between history textbooks and reading literacy skills. The strength of this correlation is influenced by the pivotal role that textbooks play during the learning process. However, there is still a need for improvement in the quality of the textbooks used, so as to further enhance students' reading literacy skills.